Income Tax System Rates (Pph) As Well As Effectiveness Towards the State in Indonesia - Ujang Badru Jaman SH, MH; Vira Yunitasari; Rizki Abdul Rozak; Raka Aditya Firmansyah; Tiara Azzahra Anzani; Ronald Christian Hindudom (Westscience Press, 2023)
Taxes are a very dominant source of state revenue. This makes taxes the backbone of state finances. Income Tax (PPh) is a tax imposed on individuals or entities on income received or accrued in a Tax Year. Income tax adheres to the Self-system Assessment System, the tax collection system is a system in which the Taxpayer himself calculates, deposits, and reports the tax owed to the Tax Service Office where he is registered. In Income Tax there are various types of rates. Income Tax is obtained as a source of state revenue. The effectiveness of Income Tax in Indonesia runs smoothly as it should. The purpose of this study is to find out how the rates of income tax and the effectiveness of income tax against the Indonesian state. Taxpayers often do not have the awareness and compliance to calculate, report, and pay their taxes owed. To overcome this problem, the Government implements Tax Sanctions. Tax sanctions can be said as a preventive tool so that taxpayers do not violate tax norms, tax sanctions are also made as a shock. therapy so that violators of tax norms do not make the same mistake again. The purpose of this study was to determine whether tax sanctions affect increasing compliance with Taxpayers namely against income tax.